Fas ligand gene transfer to the vessel wall inhibits neointima formation and overrides the adenovirus-mediated T cell response - Sata, Masataka (The National Academy of Sciences, 1998)
Proliferation of vascular smooth muscle cells (VSMCs) in response to injury plays a key role in the pathogenesis of vascular disorders. Fas ligand (FasL) induces apoptosis in Fas-bearing cells, and its expression on activated T cells contributes to the regulation of the immune response and physiological cell turnover. Here, we show that a replication-defective adenovirus encoding FasL (Ad-FasL) induced apoptosis in Fas-bearing VSMCs. When introduced locally to balloon-injured rat carotid arteries, a well characterized model of a VSMC-derived lesion, Ad-FasL functioned as a potent inhibitor of neointima formation. In rats immunized with an empty adenoviral vector, robust T cell infiltration of the vessel wall was detected after local delivery of a β-galactosidase-expressing virus (Ad-βgal), whereas T cell infiltrates were not detected after local delivery of Ad-FasL. Prior immunization prevented β-galactosidase expression from Ad-βgal, whereas the expression of the FasL transgene was unaffected. When Ad-βgal and Ad-FasL were delivered together to preimmunized animals, T cell infiltration was reduced and β-galactosidase expression was restored. These data demonstrate that Fas ligand gene transfer can effectively inhibit injury-induced vessel lesion formation and can allow adenovirus-harboring cells to evade immune destruction.